Genetic variation of technological quality in durum wheat - Nejla TURKI; Hassiba Chahdoura; Safia Elbok; Moncef Harrabi (Journal of Oasis Agriculture and Sustainable Development)
Durum wheat (Triticum durum) is a widely cultivated wheat species, with approximately 75% of global production consumed in the Mediterranean region. Its cultivation has remained a staple food for local populations, particularly in Tunisia and other Maghreb countries, where it is primarily used for pasta, couscous, and bread. Despite the widespread cultivation of wheat in Tunisia, the country is currently facing food insecurity, and the conditions under which durum wheat is grown have a significant impact on its quality-related parameters. This study aims to investigate the genetic variation of technological quality in both local and imported durum wheat varieties, with the goal of identifying useful parameters for future breeding requirements. The results indicate that the imported varieties Ismur and Portodur, which exhibit resistance to lodging and various diseases, are suitable for the needs of farmers. Additionally, the imported varieties Ismur and Silur, along with the local variety Nasr, meet the criteria for gluten and protein content, making them valuable for the semolina industry.